Unifying Culture Through Language: An Analysis of the Emergence of Classical Judeo-Arabic Writing (Journal of Comparative Study of Religions, 2023)
Saadia Gaon’s (882-942) Tafsir is considered to be a turning point in the history of not only Judeo-Arabic written production, but also medieval Judeo-Arabic culture. Through his translation of the bible into Arabic written in Hebrew characters, Saadia made this text and other works of philosophy, biblical interpretation, synagogue liturgy, and linguistics accessible to a wider audience and standardized a mode of communication among Jews throughout the medieval Islamic world. This paper compares twelfth-century Cairo Geniza fragments of Saadia’s Tafsir and Siddur, analyzing the visual interplay of Hebrew and Judeo-Arabic in these sources. Changes in color, hand, damage, marginal notes, and presence or absence of writing on the verso side of the fragment shed light on the application of Saadia’s work by Jews in the medieval Mediterranean. I ultimately conclude that while production of anti-Karaite polemic may have partially motivated Saadia to write in Judeo-Arabic, the desire to standardize a uniformly understood language rooted in Classical Arabic orthography more comprehensively explains the revolutionary effect of Saadia’s work and its immediate tenth-century adaptations outside the Rabbanite Jewish community.